Dial L for Loser : a Clique novel - Harrison, Lisi (New York : Little, Brown and Company, 2006)
Just as the Pretty Committee is getting bored with being expelled and Massie begins worrying about losing her spot as the most popular girl, Claire is cast in a Hollywood film, and as Massie and Alicia report live from the set, Kristen and Dylan keep them posted on events in Westchester County.
Ages 12 and up.
Keywords: Cliques (Sociology) -- Fiction; Fiction